Impact of vacuum gripping system oscillation on product holding force - Yakymchuk, Nikolai; Gavva, Oleksandr M. (My University, 2015)
This article discusses a possible use of vacuum gripping systems to perform process operations with multi-unit packaging equipment. A mathematical model was developed to determine a holding force for structural elements of a multi-unit package and the level of vacuum in such systems taking into account additional dynamic loads, as well as physical and mechanical properties of packages that will allow to ensure reliable holdup of structural elements of a multi-unit package and retain their marketable condition. A comparative analysis of holding force produced by standard suction cups and corrugated suction cups was conducted. The obtained results can be used to develop new types of vacuum gripping systems for multi-unit packaging.
Keywords: multi-unit package; holding force; vacuum gripping systems; multi-unit packaging equipment; транспортний пакет; сила утримування; системи вакуумного захоплення; обладнання для формування транспортних пакетів; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра мехатроніки та пакувальної техніки